PENGARUH KEPUASAN KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP LOYALITAS TENAGA PELAYANAN SOSIAL PADA PANTI SOSIAL TRESNA WERDHA BUDI MULIA JAKARTA - Restu Dwi Juliansyah (2022)
This research is a quantitive research which aims to test, find out, and prove the influence of Job Satifsaction, Work Discipline, and Work Environment on Loyalty. This research was conducted on social service workers at Panti Sosial Tresna Werdha Budi Mulia Jakarta, with total sample of 56 employees. The analysis technique used in this research is descriptive analysis and inferential analysis which consist of validity test, reliability test, coefficient of determination test, and hypothesis testing using SmartPLS 3.0. the result of this study indicate that (1) Job Satisfaction has a significant effect on Loyalty of Social Service Workers at Panti Sosial Tresna Werdha Budi Mulia Jakarta, (2) Work Discipline has no significant effect on Loyalty of Social Service Workers at Panti Sosial Tresna Werdha Budi Mulia Jakarta, (3) Work Environment has a significant effect on Loyalty of Social Service Workers at Panti Sosial Tresna Werdha Budi Mulia Jakarta, and (4) Job Satisfaction, Work Discipline, and Work Environment have a significant effect on Loyalty of Social Service Workers at Panti Sosial Tresna Werdha Budi Mulia Jakarta